1998
DOI: 10.1183/09031936.98.11061218
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary fibrosis: cytokines in the balance

Abstract: Pulmonary fibrosis can complicate diverse pulmonary and systemic pathologies. In many cases the underlying cause remains unidentified. Mortality from the disease is increasing steadily in the UK and USA. The clinical features are well-described, but patients frequently present at an advanced stage, and current treatments have not improved the poor prognosis. There is a compelling need to identify the fibrotic process earlier and to develop new therapeutic agents. Increased collagen deposition is central to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
147
0
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(156 citation statements)
references
References 30 publications
3
147
0
6
Order By: Relevance
“…The common paradigm postulates an initial alveolar injury, which triggers an inflammatory response and, subsequently, fibrosis (4). The mainstay of the current therapeutic approach to UIP is suppression of inflammation.…”
mentioning
confidence: 99%
“…The common paradigm postulates an initial alveolar injury, which triggers an inflammatory response and, subsequently, fibrosis (4). The mainstay of the current therapeutic approach to UIP is suppression of inflammation.…”
mentioning
confidence: 99%
“…[1][2][3] Transforming growth factor (TGF)-␤ is regarded as the premier pathological cytokine in chronic pulmonary fibrosis because of its enhanced presence in clinical idiopathic pulmonary fibrosis (IPF) 4,5 and its potent role in experimental fibrosis under a number of conditions. 6 -8 Interestingly, data published recently suggested that the synthesis of TGF-␤ during experimental pulmonary fibrosis was regulated by interleukin (IL) -13, 8 a Th2-type cytokine whose actions were believed to be limited to that of immune cell regulation.…”
mentioning
confidence: 99%
“…Zahlreiche experimentelle und klinische Daten legen eine über− ragende pathogenetische Rolle von TGF−â bei fibrosierenden Lungenerkrankungen nahe [46,47]. Auf in vitro Ebene konnte u. a. gezeigt werden, dass TGF−â Fibroblastenchemotaxis, Fibro− blastenproliferation und Fibroblastendifferenzierung zu Myofi− broblasten fördert und die Kollagensynthese durch Fibroblasten erheblich steigert [46].…”
Section: Rolle Von Tgf−â Und Anderer Wachstumsfaktorenunclassified
“…Die Applikation eines TGF−â−Antikörpers oder eines löslichen TGF−â−Rezeptors führt zu einer signifikanten Reduktion der pulmonale Kollagendeposi− tion in diesem Modell [49,50] [51]. Neben TGF−â scheinen auch zahlreiche weitere Wachstumsfak− toren wie PDGF (platelet−derived growth factor), CTGF (connec− tive tissue growth factor) oder IGF−I (insulin−like growth factor I) in die pathogenetische Sequenz fibrosierender Lungenerkran− kungen integriert zu sein [47].…”
Section: Rolle Von Tgf−â Und Anderer Wachstumsfaktorenunclassified